Growth curves in short supply: a descriptive study of the availability and utility of growth curve data in adolescents with eating disorders - Harrison, Megan E; Obeid, Nicole; Fu, Maeghan C Y; Norris, Mark L (Université d'Ottawa | University of Ottawa, 2013)
Healthy body weight (HBW) determination affects multiple aspects of eating disorder (ED) treatment. For example, it can inform patients and providers as to when return of menses (ROM), an objective determinant of health, can occur. Growth curves (GCs) are sensitive indicators of health in youth and when up to date provide critical information regarding normal and expected trajectories of growth. Although not widely recommended as a first line tool for HBW calculation, a GC guides providers selecting a HBW that is individualized to each patient. The primary aim of this paper was to assess availability and feasibility of utilizing GC data for HBW prediction in adolescents referred for an ED assessment. We also sought to determine how this calculation compared to the standardized HBW calculation that uses mean body mass index (BMI) for age and how each of these numbers compared to the actual weight at ROM.
Keywords: Adolescent medicine; Pediatric growth; Eating disorders